Cariprazine‐induced mania: A case series report. (27th November 2021) - Pons‐Cabrera, María T.; Palacios‐Garrán, Roberto; Tardón‐Senabre, Laia; Fernández‐Plaza, Tabatha; Marco‐Estrada, Oriol; Madero, Santiago; Anmella, Gerard; Colomer, Lluc; Druetta, Mauro; Giménez‐Palomo, Anna; Navarro‐Cortés, Lourdes; Sagué‐Vilavella, María; et al.
Abstract: Bipolar depression is the most prevalent phase of bipolar disorder (BD). There is a risk of inducing treatment‐emergent affective switches (TEAS) with antidepressants (ADs). Hence, clinical guidelines do not recommend their use in monotherapy. Cariprazine is a dopamine‐serotonin partial agonist, with a recent FDA approval as a monotherapy for BD type 1 (BD‐I) depression. To our knowledge, there is no significant evidence of cariprazine‐induced TEAS in bipolar depression. We describe three clinical cases of patients admitted to our acute psychiatric ward who developed manic episodes after the introduction of low doses of cariprazine. Two of the patients met the DSM‐5 criteria for BD‐I, and one for schizoaffective disorder, bipolar type. All patients were initially treated with low doses of cariprazine (1.5 mg) during a depressive phase. All three cases were simultaneously treated with mood stabilizers, regardless of which they switched to a manic episode when cariprazine was initiated. In our review of previous studies assessing the efficacy and side effects profile of cariprazine in BD‐I, TEAS have not been found to be significant. However, according to our experience, cariprazine may induce affective switches in BD‐I patients. Patients and psychiatrists should receive information regarding early warning symptoms and monitor possible cariprazine‐induced mood switching.